Analysis of Anxiety Levels and Compliance with Personal Protective Equipment (PPE) Use with the Occurrence of Clinical Symptoms of Covid-19 in Health Workers - Melany Pilatusalim; Sentot Imam Suprapto; Agusta Dian Ellina (Journal for Quality in Public Health, 2022)
The mental health of medical examiners in the face of Covid-19 desires to be the focal point of interest. Anxiety can release several neurotransmitters and hormones inside the body that lower the immune device so that it will be without problems inflamed with the Covid-19 virus. This observation objective is to decide the connection between the level of anxiety and adherence to the usage of PPE to the prevalence of scientific signs of Covid-19. Cross-sectional examine 102 medical experts at the principal Inpatient health facility of Usada Buana Surabaya with a proportional sampling approach. Statistical checks using the spearman-rho test. The Spearman-Rho check showed that (87.3%) of medical examiners skilled intense anxiety in managing the Covid-19 state of affairs, and more than half (62.7%) of health workers had enough compliance use of PPE when managing Covid-19 sufferers. There may be a sizeable relationship between the extent of anxiety and the occurrence of medical symptoms of Covid-19 in health workers (p-value = 0.037). There may be a substantial relationship between PPE adherence and the event of clinical signs of Covid-19 in medical examiners (p-value = zero.003). The results of this look can be a reference to screen the course of health workers with complete PPE during the Covid-19 and to reveal regular mental repute assessments, to display or investigate the psychological situation of medical experts in going through an endemic condition.